Fatty acid profile, minor bioactive constituents and physicochemical properties of insect-based oils: A comprehensive review - Yap, Jeremy Wee-Lek; Lee, Yee-Ying; Tang, Teck-Kim; Chong, Li-Choo; Kuan, Chee-Hao; Lai, Oi-Ming; Phuah, Eng-Tong (Taylor and Francis, 2023)
Insect-based food or ingredients have received tremendous attention worldwide because of their potential to ensure food and nutrition security, mitigating the reliance on land-dependent agricultural products. Indeed, insect-farming has low environmental impacts with reduced land, water and energy input. More importantly, insects are rich in high quality proteins and fats. They are also excellent sources of minerals, vitamins and bioactive compounds. Insect-based lipids are intriguing because they may contain high levels of unsaturated fatty acids particularly linoleic and α-linolenic acids. Besides, the insect-based lipids also show a considerable amount of bioactive components such as tocols, sterols and carotenoids. However, their fatty acid compositions and the nutritional values may vary depending on species, feed composition, developmental stage, geographical locations, and extraction techniques. Therefore, the present article aims to provide a comprehensive review on the fatty acid composition, the minor bioactive constituents and the physicochemical properties of fats and oils derived from insects of different orders (Coleoptera, Lepidoptera, Hymenoptera, Orthoptera, Hemiptera and Diptera). The various parameters affecting the nutritional compositions of the insect-based lipids will also be highlighted. These information will definitely provide a detailed insight on the potential applications of these fats in various food systems based on their unique properties.